Shape Recovery of Elastic Capsules from Shear Flow Induced Deformation (Communications in Computational Physics, 2014)
Red blood cells undergo substantial shape changes in vivo. Modeled asa viscoelastic capsule, their deformation and equilibrium behavior has been extensively studied. We consider how 2D capsules recover their shape, after having beendeformed to 'equilibrium' behavior by shear flow. The fluid-structure interaction ismodeled using the multiple-relaxation time lattice Boltzmann (LBM) and immersedboundary (IBM) methods. Characterizing the capsule's shape recovery with the Taylor deformation parameter, we find that a single exponential decay model suffices todescribe the recovery of a circular capsule. However, for biconcave capsules whoseequilibrium behaviors are tank-treading and tumbling, we posit a two-part recovery,modeled with a pair of exponential decay functions. We consider how these two recovery modes depend on the capsule's shear elasticity, membrane viscosity, and bendingstiffness, along with the ratio of the viscosity of the fluid inside the capsule to the ambient fluid viscosity. We find that the initial recovery mode for a tank-treading biconcave capsule is dominated by shear elasticity and membrane viscosity. On the otherhand, the latter recovery mode for both tumbling and tank-treading capsules, dependsclearly on shear elasticity, bending stiffness, and the viscosity ratio.